1979
DOI: 10.3758/bf03197595
|View full text |Cite
|
Sign up to set email alerts
|

Chunking in recall of symbolic drawings

Abstract: Three experiments explored memory for symbolic circuit drawings using skilled electronics technicians and novice subjects. In the first experiment a skilled technician reconstructed circuit diagrams from memory. Recall showed marked "chunking", or grouping, by functional units similar to Chess Masters' recall of chess positions. In the second experiment skilled technicians were able to recall more than were novice subjects following abrief exposure of the drawings. This advantage did not hold for randomly arra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
197
1
4

Year Published

1985
1985
2006
2006

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 403 publications
(216 citation statements)
references
References 9 publications
14
197
1
4
Order By: Relevance
“…In the late 1970s and 1980s, many studies demonstrated similar results to those of De Groot (1965) and Chase and Simon (1973) in a variety of curriculum areas (e.g. Egan and Schwartz 1979;Jeffries, Turner, Polson and Atwood 1981;Sweller and Cooper 1985). It is now widely accepted that expertise, including problem solving expertise, in any area, is at least heavily dependent and possibly solely dependent on knowledge held in long-term memory.…”
Section: Human Cognitive Architecture and Its Evolutionsupporting
confidence: 55%
“…In the late 1970s and 1980s, many studies demonstrated similar results to those of De Groot (1965) and Chase and Simon (1973) in a variety of curriculum areas (e.g. Egan and Schwartz 1979;Jeffries, Turner, Polson and Atwood 1981;Sweller and Cooper 1985). It is now widely accepted that expertise, including problem solving expertise, in any area, is at least heavily dependent and possibly solely dependent on knowledge held in long-term memory.…”
Section: Human Cognitive Architecture and Its Evolutionsupporting
confidence: 55%
“…Indeed, this explanation should fare well in accounting for the phenomenon with a wide array of stimuli: musical notation (Bean, 1937;Sloboda, 1974Sloboda, , 1976Weaver, 1943;Wolf, 1976), technical drawings (Egan & Schwartz, 1979), physics computations (Larkin, 1981;Larkin, McDermott, Simon, & Simon, 1980), or computer programs (McKeithern, Reitman, Reuter, & Hirtle, 1981. This is because at a general level, the processing involved in comprehending these various stimuli should be comparable (see Kintsch & van Dijk, 1978, p. 364, for a related view).…”
Section: Results and Conclusionmentioning
confidence: 99%
“…When troubleshooting familiar systems, experts can also use the case-based knowledge they gained through previous fault-finding experiences. When faced with unfamiliar systems troubleshooting, their schema-based knowledge assists them in more rapidly building a mental representation of that system than less experienced troubleshooters can (Egan & Schwartz, 1979). These sophisticated mental representations can Process-Oriented Worked Examples 5 then be used to reason about the system's (mal)functioning.…”
mentioning
confidence: 99%